Ways of Living and Knowing - Mohamed, Reem El Hassan (AUC Knowledge Fountain, 2025)
After decades of sedentarization, the Muzeina tribe in South Sinai now has new generations born into sedentary lifestyles, never experiencing nomadism like their ancestors once did. This shift has impacted their knowledge system, traditionally shaped by interactions and kinship with nature. Exposure to social media is influencing younger generations' ways of living, raising the older generations’ concerns about their Bedouin identity. Despite being one of the largest tribes in South Sinai, the Muzeina are rarely represented in literature. This ethnography explores the impact of sedentarization and contextual developments on the Muzeina's knowledge system, inherited from their ancestors. Muzeina’s relationship, and sometimes kinship, with non-human actors in ecology is critical in shaping and maintaining their traditional knowledge. Data was collected through participant observation and conversations with different generations to form solid conclusions on their mobility, ways of living, and kinship with non -human actors in the ecology, revealing the loss and retention of traditional knowledge, and their reliance, or lack thereof, on modern science. Conclusions were drawn from storytelling as well, given that storytelling is a significant practice in the Muzeina's interactions and narratives. The primary conclusion is that the Muzeina continue to practice nomadism, but they perform it differently. The Muzeina maintain bonds with non-human actors, influencing their knowledge, such as the land and its influence on their use of herbal medicine. However, younger generations' weakened relationship with some actors in the ecology network threatens the retention of traditional knowledge. Some knowledge has been lost by choice, as it no longer aligns with the Muzeina's ethos. New material influences are starting to impact their ethos and human-nonhuman kinship, posing a further threat to their knowledge systems